2016
DOI: 10.12693/aphyspola.130.1245
|View full text |Cite
|
Sign up to set email alerts
|

Hardening of (Pb,Cd)Te Crystal Lattice with an Increasing CdTe Content in the Solid Solution

Abstract: Single crystals of the (Pb,Cd)Te solid solution with CdTe content up to 9% were grown by self-selecting vapour growth method and investigated by powder X-ray diffraction, inelastic neutron scattering, and nanoindentation measurements. The analysis of the linear part of the LA phonon dispersion, determined by the inelastic neutron scattering demonstrated an increase of the sound velocity (thus the hardening of the crystal lattice) with an increase of CdTe content in the solid solution. An important increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Quite recently, we have examined selected mechanical properties of this particular semiconductor. What we have found out is an important (343) increase of the H value with an increasing Cd content in (Pb,Cd)Te solid solution [13]. At the same time, determined by us the Young modulus E remains at a constant value, at least within an experimental error.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Quite recently, we have examined selected mechanical properties of this particular semiconductor. What we have found out is an important (343) increase of the H value with an increasing Cd content in (Pb,Cd)Te solid solution [13]. At the same time, determined by us the Young modulus E remains at a constant value, at least within an experimental error.…”
Section: Introductionsupporting
confidence: 69%
“…Since 2009 several physical properties of these crystals have been both investigated and reported (see, e.g., [11][12][13][14]). Quite recently, we have examined selected mechanical properties of this particular semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…One can improve the mechanical properties of a given semiconductor by the crystal doping or alloying with another compound. Several further reports were devoted to the mechanical properties of solid solutions grown on the basis of PbTe, like, e.g., (Pb,Ge)Te or (Pb,Cd)Te (see [13][14][15][16][17] and references therein). However, such basic experimental data as anisotropy of Young's modulus (E) and that of the hardness (H) are not available for such "classical" material as PbTe.…”
Section: Introductionmentioning
confidence: 99%
“…[3], selected preliminary results of these studies can be found in Ref. [12]. In the meantime we decided to check if the IXS technique is suitable also for the accurate determination of the low-frequency phonon dispersion, observed in compounds composed of heavy elements.…”
Section: Introductionmentioning
confidence: 99%